2010
DOI: 10.1007/s00192-010-1203-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of pubocervical fascia in women with and without pelvic organ prolapse and urodynamic stress incontinence

Abstract: This pilot study is the first study to estimate changes in protein expression in the pubocervical fascia of human patients with POP. These changes could be related to the pathophysiology of POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Since myosin is responsible for muscle contraction, this overexpression of myosin light chains may be a mechanism to counteract the loss of normal urethral function in SUI. This finding is consistent with previous work showing 4.4-fold overexpression of the myosin light chains in the pubococcygeus muscle of women with POP [20].…”
Section: Discussionsupporting
confidence: 95%
“…Since myosin is responsible for muscle contraction, this overexpression of myosin light chains may be a mechanism to counteract the loss of normal urethral function in SUI. This finding is consistent with previous work showing 4.4-fold overexpression of the myosin light chains in the pubococcygeus muscle of women with POP [20].…”
Section: Discussionsupporting
confidence: 95%
“…Since myosin is responsible for muscle contraction, this overexpression of myosin heavy chains may be a mechanism to counteract the loss of normal urethral function in SUI. This finding is consistent with previous works showing overexpression myosin genes in the pubococcygeus muscle of women with POP [23] , [24] .…”
Section: Discussionsupporting
confidence: 94%
“…In label-free analysis (as in any other proteomics method), not all proteins can be resolved simultaneously; this is due to differences in their properties (such as hydrophobicity, charge, and solubility properties). The specific protocol used in our study is optimal for the solubility of cytosolic proteins [24] . Changes in the protein extraction protocol are needed for easier detection of ECM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Papers assessing the whole genome/proteome expression profile in POP did not provide consistent results (Table 1 ). Two studies on pubococcygeus tissue in POP patients have shown both up- and down-regulation of cytoskeletal genes or proteins 10 , 11 . In full-thickness vaginal wall biopsies, genes related to smooth muscle contraction, proteolysis, response to oxidative stress, transcriptional regulation, cytoskeletal organization, and lipid catabolism were over-expressed 12 .…”
Section: Resultsmentioning
confidence: 99%
“… The expression levels of transgelin (FC 54.3), smooth muscle gamma-actin (FC 6.3), myosin light polypeptide 6 (FC 4.4), and alpha-1 antitrypsin precursor (FC 4.3) were higher in patients than in controls. 2-DE western blot analysis for transgelin 11 USLs from Asian women with POP-Q stage 3-4 (cases) or 0-1 (controls) 12 cases (PM), 5 controls (PM) Microarray gene expression 143 genes were up-regulated and 87 genes were down-regulated with FC > 1.5 ( P < 0.05). The expression levels of ESRRA (FC 0.434) decreased, while the expression levels of DAPK2 (FC 2.013), IL15 (FC 2.1) and STAP2 (FC 2.392) increased in POP patients compared with controls.…”
Section: Resultsmentioning
confidence: 99%